PERSEPSI GURU DALAM PENERAPAN PENDIDIKAN BERBASIS LINGKUNGAN HIDUP PADA SEKOLAH DASAR DI MANOKWARI - Sembor, Isak; Nugroho, Bambang; Lekitoo, Merlyn N. (Universitas Papua Manokwari, 2017)
This study aims to reveal about the perception of teachers in the application of environment-based education at Elementary School in Manokwari. Environmental Education (PLH) is basically used to encourage changes made to a more environmentally friendly environment.The current facts are factors causing the implementation of PLH in Indonesia related to education teachers, among others, reducing the number of people involved in PLH, including in education in providing PLH, inadequate use of materials and methods, and facilities and infrastructure which is inadequate to be an obstacle to aid in the implementation of environmental education. Limitations of educational facilities and infrastructure are perceived by teachers who are the constraining factorsin the implementation of EE in schools.The purpose of this study is (1) to determine the perception of elementary school teachers at the elementary school level in Manokwari City, and (2) to identify elementary school teachers, and facilities and infrastructure of SD in Manokwari City based on the environment.